Women posing at a y-Walk party - Unknown:::Creator::::::::::::
Photograph shows a group portrait of women probably at D.B. Cooper's for a y-Walk party. They are wearing y-Walk stickers on their clothes and some are holding drinks in their hands. The woman in the front row is posing in a slightly crouched down position with her arms extended out to each side